Creativity of Moral Faith Teachers in Developing Educational Games to Increase Student Learning Activity - Maslia Munawaroh; Amirul Mukminin Al Anwari (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study is motivated by the importance of teacher creativity in creating engaging learning processes that can enhance students’ learning activity, particularly in Aqidah Akhlak subjects, which are often perceived as monotonous. This study aims to describe the forms of creativity exhibited by an Aqidah Akhlak teacher in developing educational games based on the Teams Games Tournament (TGT) model to enhance student learning activity at MTs Al-Munawarrah, Jambi City. A descriptive qualitative approach with a field research design was employed. The research subjects were Aqidah Akhlak teachers, with supporting informants including the school principal, other teachers, and students. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Findings reveal that the teacher developed educational games by modifying conventional games and activities, thereby successfully increasing the activity levels of most students. These findings are significant as a basis for professional development policies for madrasah teachers that go beyond providing physical facilities to building a psychological and cultural ecosystem that sustainably nurtures teacher creativity.